Resolving protein mixtures using microfluidic diffusional sizing combined with synchrotron radiation circular dichroism. Issue 1 (5th December 2018) - Bortolini, Christian; Kartanas, Tadas; Copic, Davor; Condado Morales, Itzel; Zhang, Yuewen; Challa, Pavan K.; Peter, Quentin; Jávorfi, Tamás; Hussain, Rohanah; Dong, Mingdong; Siligardi, Giuliano; Knowles, Tuomas P. J.; et al.
Abstract : Microfluidic diffusional sizing is combined with synchrotron radiation circular dichroism to resolve the secondary structure of protein mixtures. Abstract : Circular dichroism spectroscopy has become a powerful tool to characterise proteins and other biomolecules. For heterogeneous samples such as those present for interacting proteins, typically only average spectroscopic features can be resolved. Here we overcome this limitation by using free-flow microfluidic size separation in-line with synchrotron radiation circular dichroism to resolve the secondary structure of each component of a model protein mixture containing monomers and fibrils. To enable this objective, we have integrated far-UV compatible measurement chambers into PDMS-based microfluidic devices. Two architectures are proposed so as to accommodate for a wide range of concentrations. The approach, which can be used in combination with other bulk measurement techniques, paves the way to the study of complex mixtures such as the ones associated with protein misfolding and aggregation diseases including Alzheimer's and Parkinson's diseases.